NT
NT
7 tháng 7 2021 lúc 21:58

a)

ĐKXĐ: \(x\ne2\)

Ta có: \(\dfrac{1}{x-2}+3=\dfrac{3-x}{x-2}\)

\(\Leftrightarrow\dfrac{1}{x-2}+\dfrac{3\left(x-2\right)}{x-2}=\dfrac{3-x}{x-2}\)

Suy ra: \(3x-6+1=3-x\)

\(\Leftrightarrow3x+x=3+6-1\)

\(\Leftrightarrow4x=8\)

hay x=2(loại)

b) ĐKXĐ: \(x\ne7\)

Ta có: \(\dfrac{1}{7-x}=\dfrac{x-8}{x-7}-8\)

\(\Leftrightarrow\dfrac{-1}{x-7}=\dfrac{x-8}{x-7}-\dfrac{8\left(x-7\right)}{x-7}\)

Suy ra: \(x-8-8x+56+1=0\)

\(\Leftrightarrow-7x+49=0\)

\(\Leftrightarrow-7x=-49\)

hay x=7(loại)

c) ĐKXĐ: \(x\ne1\)

Ta có: \(\dfrac{5x-2}{2-2x}+\dfrac{2x-1}{2}=1-\dfrac{x^2+x-3}{1-x}\)

\(\Leftrightarrow\dfrac{5x-2}{2\left(1-x\right)}+\dfrac{\left(2x-1\right)\left(1-x\right)}{2\left(1-x\right)}=\dfrac{2-2x}{2\left(1-x\right)}-\dfrac{2\left(x^2+x-3\right)}{2\left(1-x\right)}\)

Suy ra: \(5x-2+2x-2x^2-1+x=2-2x-2x^2-2x+6\)

\(\Leftrightarrow-2x^2+8x-3=-2x^2-4x+8\)

\(\Leftrightarrow8x+4x=8+3\)

\(\Leftrightarrow12x=11\)

hay \(x=\dfrac{11}{12}\)(nhận)

Bình luận (2)
NT
7 tháng 7 2021 lúc 22:03

d) ĐKXĐ: \(x\ne\dfrac{1}{3}\)

Ta có: \(\dfrac{5-2x}{3}+\dfrac{\left(x-1\right)\left(x+1\right)}{3x-1}=\dfrac{\left(x+2\right)\left(1-3x\right)}{9x-3}\)

\(\Leftrightarrow\dfrac{\left(5-2x\right)\left(3x-1\right)}{3\left(3x-1\right)}+\dfrac{3\left(x^2-1\right)}{3\left(3x-1\right)}=\dfrac{\left(x+2\right)\left(1-3x\right)}{3\left(3x-1\right)}\)

Suy ra: \(15x-5-6x^2+2x+3x^2-3=x-3x^2+2-6x\)

\(\Leftrightarrow-3x^2+17x-8=-3x^2-5x+2\)

Suy ra: \(17x+5x=2+8\)

\(\Leftrightarrow x=\dfrac{5}{11}\)(thỏa ĐK)

e) ĐKXĐ: \(x\notin\left\{0;\dfrac{3}{2}\right\}\)

Ta có: \(\dfrac{1}{2x-3}-\dfrac{3}{x\left(2x-3\right)}=\dfrac{5}{x}\)

\(\Leftrightarrow\dfrac{x-3}{x\left(2x-3\right)}=\dfrac{5\left(2x-3\right)}{x\left(2x-3\right)}\)

Suy ra: \(x-3=10x-15\)

\(\Leftrightarrow-9x=-12\)

hay \(x=\dfrac{4}{3}\)(nhận)

Bình luận (0)
NT
7 tháng 7 2021 lúc 22:13

a) \(\dfrac{1}{x-2}+3=\dfrac{3-x}{x-2}\)

dktc : x ≠ 2

MTC : x - 2

Quy đồng mẫu thức hai vế của phương trình : 

⇒ \(\dfrac{1}{x-2}+\dfrac{3\left(x-2\right)}{x-2}=\dfrac{3-x}{x-2}\)

Suy ra : 1 + 3(x -  2) = 3 - x

         \(\Leftrightarrow\) 1 + 3x - 6 - 3 + x = 0

        \(\Leftrightarrow\) 4x - 8 = 0

        \(\Leftrightarrow\) 4x = 8

        \(\Leftrightarrow\) x = \(\dfrac{8}{4}=2\) (không thỏa mãn)

 Vậy S = ∅

b) \(\dfrac{1}{7-x}=\dfrac{x-8}{x-7}-8\)

    \(\dfrac{-1}{x-7}=\dfrac{x-8}{x-7}-8\)

dkxd : x ≠ 7

MTC : x - 7

Quy đồng mẫu thức hai vế của phương trình : 

\(\Rightarrow\) \(\dfrac{-1}{x-7}=\dfrac{x-8}{x-7}-\dfrac{8\left(x-7\right)}{x-7}\)

Suy ra : -1 = x - 8 - 8(x - 7)

          \(\Leftrightarrow\) -1 = x - 8 - 8x + 56

          \(\Leftrightarrow\) -1 - x + 8 + 8x - 56 = 0

          \(\Leftrightarrow\) -49 + 7x = 0

          \(\Leftrightarrow\) 7x = 49

          \(\Leftrightarrow\) x = \(\dfrac{49}{7}=7\) (không thỏa mãn)

 Vậy S = ∅ 

c) \(\dfrac{5x-2}{2-2x}+\dfrac{2x-1}{2}=1-\dfrac{x^2+x-3}{1-x}\)

    \(\dfrac{5x-2}{2\left(1-x\right)}+\dfrac{2x-1}{2}=1-\dfrac{x^2+x-3}{1-x}\)

dkxd : x ≠ 1

MTC : 2(1 - x)

Quy đồng mẫu thức hai vế của phương trình : 

\(\Rightarrow\) \(\dfrac{5x-2}{2\left(1-x\right)}+\dfrac{\left(2x-1\right)\left(1-x\right)}{2\left(1-x\right)}=\dfrac{2\left(1-x\right)}{2\left(1-x\right)}\) - \(\dfrac{2\left(x^2+x-3\right)}{2\left(1-x\right)}\)

Suy ra : 5x - 2 + (2x - 1)(1 - x) = 2(1 - x) - 2(x2 + x - 3)

         \(\Leftrightarrow\) 5x - 2 + 3x - 2x2 - 1 = 2 - 2x - 2x2 - 2x + 6

         \(\Leftrightarrow\) 5x - 2 + 3x - 2x2 - 1 - 2 + 2x + 2x2 + 2x - 6 = 0

         \(\Leftrightarrow\) 12x - 11 = 0

         \(\Leftrightarrow\) 12x = 11

         \(\Leftrightarrow\) x = \(\dfrac{11}{12}\) (thỏa mãn)

 Vậy S = \(\left\{\dfrac{11}{12}\right\}\)

d) \(\dfrac{5-2x}{3}+\dfrac{\left(x-1\right)\left(x+1\right)}{3x-1}=\dfrac{\left(x+2\right)\left(1-3x\right)}{9x-3}\)

   \(\dfrac{5-2x}{3}+\dfrac{\left(x-1\right)\left(x+1\right)}{3x-1}=\dfrac{\left(x+2\right)\left(1-3x\right)}{3\left(3x-1\right)}\)

dkxd : x ≠ \(\dfrac{1}{3}\) 

 MTC : 3(3x - 1)

Quy đồng mẫu thức hai vế của phương trình : 

\(\Rightarrow\) \(\dfrac{\left(5-2x\right)\left(3x-1\right)}{3\left(3x-1\right)}+\dfrac{3\left(x-1\right)\left(x+1\right)}{3\left(3x-1\right)}\) = \(\dfrac{\left(x+2\right)\left(1-3x\right)}{3\left(3x-1\right)}\)

Suy ra : (5 - 2x)(3x - 1) + 3(x - 1)(x + 1) = (x + 2)(1 - 3x)

          \(\Leftrightarrow\) 17x - 5 - 6x2 + 3(x2 - 1) = -5x - 3x2 + 2

          \(\Leftrightarrow\) 17x - 5 - 6x2 + 3x2 - 3 + 5x + 3x2 - 2 = 0

          \(\Leftrightarrow\) 22x - 10 = 0

          \(\Leftrightarrow\) 22x = 10

          \(\Leftrightarrow\) x = \(\dfrac{10}{22}=\dfrac{5}{11}\) (thỏa mãn)

 Vậy S = \(\left\{\dfrac{5}{11}\right\}\)

 Chúc bạn học tốt

 

Bình luận (1)
NT
7 tháng 7 2021 lúc 23:08

f)

ĐKXĐ: \(x\notin\left\{-\dfrac{3}{4};5\right\}\)

Ta có: \(\dfrac{x^3-\left(x-1\right)^3}{\left(4x+3\right)\left(x-5\right)}=\dfrac{7x-1}{4x+3}-\dfrac{x}{x-5}\)

\(\Leftrightarrow\dfrac{x^3-x^3+3x^2-3x+1}{\left(4x+3\right)\left(x-5\right)}=\dfrac{\left(7x-1\right)\left(x-5\right)}{\left(4x+3\right)\left(x-5\right)}-\dfrac{x\left(4x+3\right)}{\left(4x+3\right)\left(x-5\right)}\)

Suy ra: \(3x^2-3x+1=7x^2-35x-x+5-4x^2-3x\)

\(\Leftrightarrow3x^2-3x+1=3x^2-39x+5\)

\(\Leftrightarrow-3x+39x=5-1\)

\(\Leftrightarrow36x=4\)

hay \(x=\dfrac{1}{9}\)(thỏa ĐK)

g)

ĐKXĐ: \(x\notin\left\{2;5\right\}\)

Ta có: \(\dfrac{3x}{x-2}-\dfrac{x}{x-5}=\dfrac{3x}{\left(x-2\right)\left(5-x\right)}\)

\(\Leftrightarrow\dfrac{3x\left(x-5\right)}{\left(x-2\right)\left(x-5\right)}-\dfrac{x\left(x-2\right)}{\left(x-2\right)\left(x-5\right)}=\dfrac{-3x}{\left(x-2\right)\left(x-5\right)}\)

Suy ra: \(3x^2-15x-x^2+2x+3x=0\)

\(\Leftrightarrow2x^2-9x=0\)

\(\Leftrightarrow x\left(2x-9\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\left(nhận\right)\\x=\dfrac{9}{2}\left(nhận\right)\end{matrix}\right.\)

Bình luận (0)

Các câu hỏi tương tự
H24
Xem chi tiết
NH
Xem chi tiết
TL
Xem chi tiết
TV
Xem chi tiết
HD
Xem chi tiết
TL
Xem chi tiết
DA
Xem chi tiết
TL
Xem chi tiết
ND
Xem chi tiết
UN
Xem chi tiết